MENINGKATKAN KETERAMPILAN MENYIMAK BERITA MELALUI TELEVISI DENGAN MENGGUNAKAN STRATEGI PEMBELAJARAN THE POWER OF TWO DI SMP - Setiana, Aslinda Hadi; Syam, Christanto; Saman, Sisilya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
1 This research is based on the facts in the field that show the results of learning to listening the news has not achieved the expected results. This is because teachers are still using conventional learning model, less varied and less interesting, so that students' activities seem monotonous in following the learning. This research  were conducted in three cycles. Each cycle consists of planning, acting, observation, and reflection. The research method used is descriptive method, the research form is qualitative, and the type of research is classroom action research (PTK). The results showed that the learning strategy of The Power Of Two can improve  the ability of teacher in planning and actingof news gathering learning  1 plan to learning.  On the first cycle, the score was 46,40, the second cycle the score was 47,00 and third cycle the score was 48,00.  All thethird score is on verygood categorized.  APKG 2 of the teacher acts on the learning, the score in cycle 1 it 39,00 which in good categorized. Cycle 2 and 3 the score in 42,67 and 45,67 which in very good categorized.   Keywords: Listening, news, strategy The Power of Two